Exploitation shifted trophic ecology and habitat preferences of Mediterranean and Black Sea bluefin tuna over centuries - Adam J. Andrews; Christophe Pampoulie; Antonio Di Natale; Piero Addis; Darío Bernal‐Casasola; Veronica Aniceti; Gabriele Carenti; Verónica Gómez‐Fernández; Valerie Chosson; Alice Ughi; Matt Von Tersch; Maria Fontanals‐Coll; et al. (Fish and Fisheries, 2023)
During recent decades, the health of ocean ecosystems and fish populations has been threatened by overexploitation, pollution and anthropogenic‐driven climate change. Due to a lack of long‐term ecological data, we have a poor grasp of the true impact on the diet and habitat use of fishes. This information is vital if we are to recover depleted fish populations and predict their future dynamics. Here, we trace the long‐term diet and habitat use of Atlantic bluefin tuna (BFT), Thunnus thynnus , a species that has had one of the longest and most intense exploitation histories, owing to its tremendous cultural and economic importance. Using carbon, nitrogen and sulphur stable isotope analyses of modern and ancient BFT including 98 archaeological and archival bones from 11 Mediterranean locations ca. 1st century to 1941 CE, we infer a shift to increased pelagic foraging around the 16th century in Mediterranean BFT. This likely reflects the early anthropogenic exploitation of inshore coastal ecosystems, as attested by historical literature sources. Further, we reveal that BFT which migrated to the Black Sea–and that disappeared during a period of intense exploitation and ecosystem changes in the 1980s–represented a unique component, isotopically distinct from BFT of NE Atlantic and Mediterranean locations. These data suggest that anthropogenic activities had the ability to alter the diet and habitat use of fishes in conditions prior to those of recent decades. Consequently, long‐term data provide novel perspectives on when marine ecosystem modification began and the responses of marine populations, with which to guide conservation policy.

Human and animal subsistence in northern Iberia during the Late Chalcolithic-Bronze Age: biomolecular insights from Muela de Borja, Ebro Valley - Laura C. Viñas-Caron; Isidro Aguilera; Tina Jakob; Joe W. Walser; Luke Spindler; Maria Fontanals-Coll; Michelle Alexander (Archaeological and Anthropological Sciences, 2022)

Long-term dietary change in Atlantic and Mediterranean Iberia with the introduction of agriculture: a stable isotope perspective - Miriam Cubas; Rita Peyroteo-Stjerna; Maria Fontanals-Coll; Laura Llorente-Rodríguez; Alexandre Lucquin; Oliver Edward Craig; André Carlo Colonese (Archaeological and Anthropological Sciences, 2019)

Human diet and the chronology of neolithic societies in the north-east of the Iberian Peninsula: the necropolises of Puig d’en Roca and Can Gelats (Girona, Spain) - Juan F. Gibaja; Maria Fontanals-Coll; Stephanie Dubosq; F. Xavier Oms; Anna Augé; Francisco Javier Santos; Berta Morell; M. Eulàlia Subirà (Archaeological and Anthropological Sciences, 2017)